A Dynamic Model of Endogenous Trade Policy - Beverly J. Lapham; Roger Ware (Queen's University, Department of Economics, 1993)
A puzzle in the analysis of trade policy is why free trade outcomes, which maximize world income, are not more often observed. One reason is that economics agents with special interests affect both the form and level of international protective policies. This paper investigates the dynamic interaction of special interest groups and highlights endogenous links between current policies and future policies. We explore these intertemporal links in a general equilibrium environment in which lobbying activity and tariff policies are the outcome of a dynamic game among interest groups located in both countries. In the Markov perfect equilibrium, future policies are affected by current policies as the current trade regime affects the ability and the willingness of these groups to lobby for future policies which favor their interests. An unusual feature of the economy is that the transition probabilities over trading regimes are endogenous. The average length of a trade war can be computed as a function of these probabilities, and we show that it is increasing in the agents' degree of risk aversion. In addition, due to deadweight losses associated with lobbying, expected aggregate welfare in a lobbying equilibrium is generally below autarkic welfare.
Keywords: F13; C73; 330